2001
DOI: 10.1080/152873901300007824
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Daily Dermal Application of Deet and Permethrin, Alone and in Combination, on Sensorimotor Performance, Blood-Brain Barrier, and Blood-Testis Barrier in Rats

Abstract: DEET and permethrin were implicated in the development of illnesses in some veterans of the Persian Gulf War. This study was designed to investigate the effects of daily dermal application of these chemicals, alone or in combination, on the permeability of the blood-brain barrier (BBB) and blood-testes barrier (BTB) and on sensorimotor performance in male Sprague-Dawley rats. Groups of five rats were treated with a dermal daily dose of 4, 40, or 400 mg/kg DEET in ethanol or 0.013, 0.13, or 1.3 mg/kg permethrin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(11 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…Such permeabilization will be expected of course to increase chemical access to the CNS and thus increase chemical sensitivity generated in the CNS. Increased blood-brain barrier permeability in response to chemical exposure has been reported by Abou-Donia and co-workers in a rat model of MCS (119). Evidence suggesting such increased permeability has been reviewed for the related conditions of PTSD (29) and CFS (120).…”
Section: Two Accessory Mechanisms In Mcs: Increased Blood-brain Barrimentioning
confidence: 89%
“…Such permeabilization will be expected of course to increase chemical access to the CNS and thus increase chemical sensitivity generated in the CNS. Increased blood-brain barrier permeability in response to chemical exposure has been reported by Abou-Donia and co-workers in a rat model of MCS (119). Evidence suggesting such increased permeability has been reviewed for the related conditions of PTSD (29) and CFS (120).…”
Section: Two Accessory Mechanisms In Mcs: Increased Blood-brain Barrimentioning
confidence: 89%
“…Early animal models of PB established that this drug can adversely affect nerve function ( Drake-Baumann & Seil, 1999 ; Hudson, Foster, & Kahng, 1985 ) and can also have gastrointestinal ( Kluwe, Page, Toft, Ridder, & Chung, 1990 ), muscular ( Adler, Deshpande, Foster, Maxwell, & Albuquerque, 1992 ), immune ( Peden-Adams et al, 2004 ) and cardiovascular ( Bernatova, Babal, Grubbs, & Morris, 2006 ) effects. Rodents given PB over time showed a number of locomotor, learning and behavioral deficits ( Abou-Donia, Dechkovskaia, Goldstein, Bullman, & Khan, 2002 ; Abou-Donia et al, 2001 ; van Haaren et al, 2001 ), despite showing no overt signs of cholinergic toxicity or illness. Three studies in rodent models found that the adverse effects of PB were enhanced by stressors ( Abdel-Rahman, Abou-Donia, El-Masry, Shetty, & Abou-Donia, 2004 ; Abdel-Rahman, Shetty, & Abou-Donia, 2002 ; Friedman et al, 1996 ).…”
Section: Animal Models Of Gwi Etiology and Pathologymentioning
confidence: 99%
“…Abou-Donia et al (2001) observed that clinical conditions of rats treated with daily dermal applications of 4, 40, and 400 mg/kg BW DEET in ethanol were not different from the controls. There were also no differences observed in the weight of treated animals when compared to the controls Abou-Donia et al, 2001). However, Abou-Donia et al (2001) suggested that exposures to DEET at 40 and 400 mg/kg BW for 60 days decreased blood-brain barrier permeability in certain brain regions, which may have important physiological or pharmacological consequences.…”
Section: Subchronic Toxicitymentioning
confidence: 86%